Optional Copyright Renewal? Lessons for Designing Copyright Systems: 28th Annual Horace S. Manges Lecture, February 23, 2015 - Reese, R. Anthony (The Columbia Journal of Law & the Arts, 2016)
When Register of Copyrights Maria Pallante gave the Manges Lecture two years ago, she suggested that we explore drafting the “Next Great Copyright Act.”1 Creating that Act will require hard thinking about how to adapt copyright law to meet the challenges of our current legal, cultural, and technological era. But even with great ideas about how to adapt the law, creating the Next Great Copyright Act will also require designing a copyright statute that implements those ideas. Tonight, I’d like to explore the constraints and complexities that will confront the copyright bar as we try to design particular features of a “Next Great Copyright Act.” As we think about copyright law revision, many different people will want to rewrite many different statutory provisions in many different ways. Revision ideas that have already been mentioned involve statutory licensing, public performance rights for sound recordings, recordation of transfers,2 statutory damages, orphan works, a resale royalty for visual artists, federal protection for pre-1972 sound recordings, incidental copies, and digital first sale, just to name a few.